Exploring the Impact of Financial Inclusion in Community Development in Cowdray Park, Bulawayo - Mutale, Ncobeni M; Moyo, Gorden; Tshuma, Mercy; Malinga, Wayne (Archives of Business Research, 2025)
Financial inclusion plays a crucial role in socioeconomic development, particularly in low-income communities. It is upon this premise that this study examines the impact of financial inclusion on the development of Cowdray Park, a growing suburb in Bulawayo, Zimbabwe. study explores the level of financial inclusion, its relationship with household income, and its impact on savings, entrepreneurship, and overall well-being. Using a qualitative research approach, data was gathered through focus group discussions and semi-structured interviews. As part of its findings, Cowdray Park residents face significant barriers to financial inclusion, such as limited access to formal financial services, low financial literacy, and high levels of poverty and unemployment. However, the study demonstrates a positive correlation between financial inclusion and household income. Increased access to financial services is perceived to empower individuals, stimulate entrepreneurship, and improve the overall quality of life in the community. To improve financial inclusion in Cowdray Park, recommendations include expanding formal financial services through agent banking, promoting financial literacy, and implementing policies to reduce barriers to financial inclusion in order to foster community development.